The role of oxygen in shockwave-synthesized γ-Si3N4 material. Issue 12 (October 2015) - Köhler, A.; Schlothauer, T.; Schimpf, C.; Klemm, V.; Schwarz, M.; Heide, G.; Rafaja, D.; Kroke, E.
Abstract The high pressure spinel-type γ-Si3N4 was prepared by using shock wave synthesis from amorphous precursors at the peak shock pressures around 34 GPa. Due to the high liability of the precursor to oxidation, it is nearly impossible to obtain oxygen-free high-pressure material. The overall oxygen content varies between 7 and 12 wt%. However, the X-ray and neutron diffraction experiments confirmed that the spinel-like phase dominates the samples. The neutron diffraction revealed that up to 5 wt% of oxygen can be accommodated in the crystal structure of γ-Si3N4, where it replaces nitrogen. Additional oxygen seemed to increase the amount of an amorphous phase in the samples. The local chemical analysis in a transmission electron microscope proved that the amorphous phase contains more oxygen than the crystalline phase, thus the excess of oxygen was verified to be contained in the amorphous phase.